Identificación de trypanosoma cruzi en los habitantes del sector Lourdes del cantón Portovelo. - Jiménez Loyola, Lilia Elizabeth (2013)
The American tripanosomiasis or illness of Chagas is potentially an affection human and it constitutes an important problem of public health mainly in the American continent in the countries of Latin America where it is endemic, it is transmitted to the human beings mainly by the feces of insects well-known triatomíneos as vinchucas or chinchorro. The Sector Lourdes belonging to the Canton Portovelo an endemic area is considered in which the presence of the vectorial triatoma "chinchorro" has been evidenced in most of the housings, because they are built of cane, wood and tile. This parasite affects children, youths and adults that have had frequent contact with earth, so much straws, bushes, domestic animals mainly wild, it is hence that he was carried out the present study of investigation of descriptive-traverse type, with the objective of to identify Trypanosoma cruzi and to determine the presence of antibodies against Trypanosoma cruzi; in a sample of 102 inhabitants that you/they fulfilled the inclusion approaches, it was used the method thick direct drop and ELISA'S technique, reaching the conclusions: that 100% of the inhabitants doesn't present the parasite by means of the exam of thick drop and a seropositivity IgG or IgM of 6 cases by means of ELISA'S test that you/they represent 6%. Key words: Trypanosoma cruzi, Thick Drop, ELISA.